Prevalence and molecular characterization of Spirometra erinaceieuropaei spargana in snakes in Hunan Province, China. (27th February 2020) - Liu, W.; Tan, L.; Huang, Y.; Li, W.C.; Liu, Y.S.; Yang, L.C.
Abstract: Sparganosis is an important foodborne parasitic zoonosis; however, few reports on the prevalence of snake-infecting plerocercoids from Hunan province in China are available. Therefore, we investigated the prevalence of spargana infection in wild snakes from this region in 2018, and identified an astonishing prevalence rate of 91.7% (344/375). Spargana parasites were found in 99.1% of Zaocys dhumnades, 94.1% of Elaphe carinata and 86.7% of Elaphe taeniura . Parasites exhibited various distributions: 50% were located in muscular tissue, 32.1% in subcutaneous tissue and 17.9% in the coelomic cavity. To identify the specific status of spargana collected from wild snakes, partial mitochondrial cytochrome c oxidase subunit 1 ( cox 1) gene sequences were amplified, sequenced and analysed. Sequence variations for cox 1 among all the examined plerocercoids ranged between 0.0 and 2.9%, with 21 variable sites identified (4.71%, 21/446). Phylogenetic analyses identified that all plerocercoids isolated from Hunan province were Spirometra erinaceieuropaei . This is the first report of S. erinaceieuropaei infection in snakes in Hunan province. The risks and harms of sparganosis should be publicized, and illegal wildlife trade should be controlled.